Mapping the 3D position of battery cathode particles in Bragg coherent diffractive imaging. (16th February 2023) - Shabalin, A. G.; Zhang, M.; Yao, W.; Rysov, R.; Ren, Z.; Lapkin, D.; Kim, Y.-Y.; Assalauova, D.; Mukharamova, N.; Sprung, M.; Vartanyants, I. A.; Meng, Y. S.; et al.
Abstract : A method to determine the 3D position of particles in Bragg coherent diffractive imaging experiments is proposed. Test measurements demonstrate depth‐resolution with a precision of 20 µm along the beam. Abstract : In Bragg coherent diffractive imaging, the precise location of the measured crystals in the interior of the sample is usually missing. Obtaining this information would help the study of the spatially dependent behavior of particles in the bulk of inhomogeneous samples, such as extra‐thick battery cathodes. This work presents an approach to determine the 3D position of particles by precisely aligning them at the instrument axis of rotation. In the test experiment reported here, with a 60 µm‐thick LiNi0.5 Mn1.5 O4 battery cathode, the particles were located with a precision of 20 µm in the out‐of‐plane direction, and the in‐plane coordinates were determined with a precision of 1 µm.